A política nacional da educação especial na perspectiva da educação inclusiva: artefato digital como possibilidade de desenvolvimento da identidade e da cultura da pessoa surda gaúcha - Cordero, Bibianna Ferrão (2022)
Public policies aimed at inclusive education represent a civilizing advance when it comes to guaranteeing the rights and citizenship of people with disabilities. The present study has as its central theme inclusive public policies and the construction of deaf culture and identity. The main objective sought to innovate the inclusive process through the production of a digital artifact: Glossary Gauchesco in Libras, focused on the specificities of the gaucho language, enabling the development of the identity and culture of the deaf person. As specific objectives, Creation of the Gaucho Forum for the Deaf at the Gaucho Music Festival “Coxilha Nativista” reflecting on the specificities of the Gaucho language for Libras, facilitating the development of the identity and culture of the Gaucho deaf person.; Revisit the main Public Policies aimed at Inclusive Education, focusing on the area of inclusion of the deaf. The methodological path was chosen for the qualitative approach in the contributions of Minayo (2005) and autobiographical narrative Josso (2010) was carried out with the subjects of the deaf community of Riograndense. This dissertation resulted in the product: https://www.youtube.com/@forumgauchescodesurdos/featured. To follow this path, the conceptual singularity Vygotsky (1996, 2003), Skliar (1997, 1999, 2005), Gesser (2009), Quadros (1997, 2004, 2006) and the regulations of the main Public Policies aimed at people with disabilities, inclusive education and deafness. We believe that the construction of the digital artifact: Glossary Gauchesco in Libras can be considered an innovative practice for the translation and interpretation of Libras in the regional context, in the state of Rio Grande do Sul, as a support for translation and sociocultural mediations.